Distribution of PM2.5 in Thailand - Phumuanboot, Thanawat; Ngamjarus, Chetta (Srinakharinwirot University Journal of Sciences and Technology, 2026)
Particulate Matter with a diameter of less than 2.5 microns (PM2.5) is an air pollution that affects the health of Thai people. Thus, this study aims to investigate the spatial distribution of PM2.5 in Thailand. We retrieved PM2.5 data during 2020 to 2024 from the website of Pollution Control Department, Ministry of Natural Resources and Environment, Thailand. We explored a spatial autocorrelation of the PM2.5 by using Moran’s I test and Local Indicator of Spatial Autocorrelation (LISA). The results indicated that the annual average of PM2.5 concentration increased by approximately 4.4 µg/m³ between 2022 and 2024.The distribution of PM2.5 in 2024 was strongest clustering pattern (Global Moran’s I = 0.66, 95% confidence Interval: 0.29 to 0.99). When we conducted spatial analysis by using provincial data, our findings reveal that northern part of Thailand had the highest in both quantity and spread of PM2.5 in 2020, 2023, and 2024. Additionally, we also found that the majority of southern region of Thailand had lowest of average PM2.5 over the past five years. When monthly data of PM2.5 was considered, the findings found that quantity of PM2.5 was highest between January and April each year.